2015
DOI: 10.1039/c5nr04246a
|View full text |Cite
|
Sign up to set email alerts
|

Visible emission from Ag+exchanged SOD zeolites

Abstract: Broad visible emissions dominant at green or red have been observed for the thermally-treated Ag(+) exchanged SOD zeolites, determined by the Ag(+) loading contents and the excitation wavelengths. Contrary to the notable reversible green/red dominant emission evolution in the Ag(+) exchanged LTA zeolites upon hydration/dehydration in air (or water vapor)/vacuum, emission spectra of the Ag(+) exchanged SOD zeolites are insensitive to the environmental change. This is most probably due to the difficult H2O perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…The X-ray diffraction (XRD) results of the as-synthesized SOD zeolites are presented in Fig. 1b, which were well consistent with a previous report, 28 indicating the successful synthesis of the SOD zeolites. The luminescent phosphors were prepared by incorporating Ag + ions into the as-synthesized SOD zeolites and then heated at different temperatures (200 °C or 300 °C) in air atmosphere for 3 h, 6 h, 9 h or 12 h. According to the addition amounts of Cs + and Ag + in the initial solution, we obtained partially exchanged zeolites denoted as y Ag-SOD or x Cs- y Ag-SOD.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The X-ray diffraction (XRD) results of the as-synthesized SOD zeolites are presented in Fig. 1b, which were well consistent with a previous report, 28 indicating the successful synthesis of the SOD zeolites. The luminescent phosphors were prepared by incorporating Ag + ions into the as-synthesized SOD zeolites and then heated at different temperatures (200 °C or 300 °C) in air atmosphere for 3 h, 6 h, 9 h or 12 h. According to the addition amounts of Cs + and Ag + in the initial solution, we obtained partially exchanged zeolites denoted as y Ag-SOD or x Cs- y Ag-SOD.…”
Section: Resultssupporting
confidence: 90%
“…This implies that the atom number of the silver nanoclusters gradually increases as the Ag loading increases, which is in good agreement with the results reported previously. 23,28…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that the reduction of Ag + for the formation of Ag NCs requires electrons, which can be obtained from O 2− in hydration water or the zeolite framework; the corresponding reaction can be described as 4Ag + + 2O 2− → 4Ag 0 + O 2 ↑. 5,33,38,47,48 Previous studies suggested that the coexistence of RE ions such as Eu 3+ and Tb 3+ can suppress the above reaction by isolating Ag + from water molecules or bonding with the framework oxygen, therefore hindering the formation of Ag NCs. 2,16,40 This is consistent with our XPS results in Table 1 that with the loading and increased loading amount of Tb 3+ , the atomic percentage of O left increased from 52.13 to 65.21%, indicative of less efficient Ag NCs formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The fact that Ag-exchanged zeolites exhibit luminous properties despite containing no rare earth metal component indicates zeolite as a promising luminescent material for future use. In recent years, many researchers have investigated the luminescence behavior of silver-exchanged zeolites [10][11][12][13][14][15][16][17][18]. Many reports have described that Ag clusters formed with a zeolite framework are luminescent species.…”
Section: Introductionmentioning
confidence: 99%